2007
DOI: 10.1073/pnas.0709778104
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hypothalamic malonyl-CoA by central glucose and leptin

Abstract: Hypothalamic malonyl-CoA has been shown to function in global energy homeostasis by modulating food intake and energy expenditure. Little is known, however, about the regulation of malonyl-CoA concentration in the central nervous system. To address this issue we investigated the response of putative intermediates in the malonyl-CoA pathway to metabolic and endocrine cues, notably those provoked by glucose and leptin. Hypothalamic malonyl-CoA rises in proportion to the carbohydrate content of the diet consumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
85
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 31 publications
(57 reference statements)
4
85
0
1
Order By: Relevance
“…Because AMPK catalyzes the phosphorylation/activation of acetyl-CoA carboxylase (ACC), it follows that a decrease in AMPK activity leads to dephosphorylation and activation of hypothalamic ACC. Consistent with this scenario we found that the central administration of glucose increases hypothalamic malonyl-CoA, decreases orexigenic neuropeptide expression, increases anorexigenic neuropeptide expression and suppresses food intake (9). Similar effects were elicited by feeding a high-carbohydrate diet after food deprivation.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…Because AMPK catalyzes the phosphorylation/activation of acetyl-CoA carboxylase (ACC), it follows that a decrease in AMPK activity leads to dephosphorylation and activation of hypothalamic ACC. Consistent with this scenario we found that the central administration of glucose increases hypothalamic malonyl-CoA, decreases orexigenic neuropeptide expression, increases anorexigenic neuropeptide expression and suppresses food intake (9). Similar effects were elicited by feeding a high-carbohydrate diet after food deprivation.…”
supporting
confidence: 71%
“…2-DG blocked this effect, responses characteristic of glucose (ref. 9 and Fig. 1B) rather than fructose.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In rats, for example, central administration of fructose increases appe-tite and energy intake (Cha et al, 2008). The rapid decrease in ATP levels associated with fructose metabolism is assumed to activate AMP kinase and inhibit the down-stream production of malonyl-co-A, a known appetite suppressant (Wolfgang et al, 2007). This in turn leads to stimulation of the anorexigenic neurocircuitry (decreased levels of cocaine and amphetamine-regulated transcript and proopiomelanocortin) in the hippocampus, and increased activity of the orexigenic pathway (reduced levels of neuropeptide Y and agouti-related peptide) (Cha et al, 2008).…”
Section: Fructose and Metabolic Flexibilitymentioning
confidence: 99%